Measurements of elemental iodine in soy sauces in Taiwan using a modified microplate method - Huang, Chun-Jui; Lee, Lin-Hsuan; Cheng, Cheng-Pin; Yao, Shan-Fan; Chen, Harn-Shen; Hwu, Chii-Min; Tang, Kam-Tsun; Wang, Fan-Fen; Shih, Chiao-Wei; Yang, Chen-Chang; Huang, Wen-Sheng (Frontiers in Endocrinology, 2023)
Background: Soy sauce is widely used in a variety of Asian dishes to enhance flavor. Soybean and most soybean products, including soy sauces, are listed as prohibited foods in a low iodine diet. However, the iodine content in soy sauces is largely unknown. The aim of this study was to determine the iodine content in domestic soy sauces in Taiwan. Methods: Twenty-five different kinds of soy sauces were diluted with distilled water and with a dilution factor of fifty or above. Iodine concentrations of the diluted samples were measured colourimetrically based on the Sandell-Kolthoff reaction by a modiﬁed microplate method. All the measurements were repeated twelve times on three different days for determination of mean and standard deviation (SD), and coefficients of variance (CV). Serial dilution and recovery tests were also performed for validation. The results were confirmed by an inductively coupled plasma mass spectrometry (ICP-MS) method. Results: Among the twenty-five surveyed soy sauces, most of them (n=22) were iodine-free (<16 ug/L, and thus un-detectable). The iodine concentrations (mean ± SD) of the three iodine-containing soy sauces were 2.7 ± 0.1, 5.1 ± 0.2, and 10.8 ± 0.6 mg/L, respectively. The inter-assay, intra-assay and total CVs were all <5.3% for the modified microplate method. The results obtained by ICP-MS were consistent with those of the modified microplate method. The recovery rates in the serial dilution test and recovery test ranged from 94.7% to 118.6%. Two of the three iodine-containing soy sauces were supplemented with kelp extract, while the other one without kelp extract had the highest amount of salt among the three iodine-containing soy sauces. Therefore, we postulate that iodized salt instead of kelp extract is the source of higher iodine content in that sauce. Conclusion: The results suggest that most soy sauces are iodine-free and may be allowed during low iodine diets.